The Effect of Financial Literacy, Access to Capital, and Interest in Using E-Commerce on SMEs Performance (Study of SMEs in Blitar) - Junaidi, Junaidi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the effect of financial literacy, access to capital, and interest in using e-commerce on the performance of SMEs in Blitar City. This research is quantitative research with a correlational research approach. The population in this study were SMEs registered at the Blitar SMEs Office, and the sample in this study was 75 respondents with a sampling technique using purposive sampling. The data used in this study is primary data in the form of questionnaires distributed to respondents and measured using a Likert scale. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that (1) financial literacy has a positive and significant effect on SMEs’ performance, (2) access to capital has a positive and significant effect on SMEs’ performance, and (3) interest in using e-commerce has a positive and significant effect on SMEs’ performance.